Virals and youth speak - Wileczek, Anna (Papers in Linguistics, 2025)
The article examines the phenomenon of (verbal) virals in the informal online discourse of young people. Multi-word structures, with the status of minimal text or quotation and an undefined (contextual) genological status (sayings, retorts, comments), when excerpted from their original context gain popularity through numerous shares, comedic transformations, and ironic parodies. Hence, it becomes essential to determine the performative process (community creation) that contributes to the viral nature of a particular structure. Using methods of cultural cartography and semantic-pragmatic analysis, the article identifies and discusses examples of functions through which the content influences the audience (playful, identity-forming, tribal, educational, creative, affect regulatory, and inspiring-motivational).